Weight Loss Following Roux-en-Y Gastric Bypass Surgery: A Systematic Review of Psychosocial Predictors - Sockalingam, Sanjeev; Hawa, Raed; Wnuk, Susan; Strimas, Rachel; H. Kennedy, Sidney (Current Psychiatry Reviews, 2011)
Objective: Weight loss surgery has been heralded as a treatment alternative for patients with morbid obesity. Psychiatric disorders are highly prevalent in bariatric surgery candidates and a myriad of psychosocial variables has been explored to identify mediators of post-surgery weight loss. The following review aims to elucidate psychosocial predictors of weight loss outcomes specific to Roux-en-Y gastric bypass surgery (RYGBS). Methods: We searched PubMed for prospective trials evaluating psychosocial predictors for weight loss with RYGBS published between 2000 and 2010. Manual searches of references listed in review articles, case series and anecdotal reports supplemented our literature search. Additional literature on post-bariatric surgery psychosocial outcomes and management of psychiatric sequelae in bariatric surgery patients are discussed in this review. Results: A total of 20 prospective studies were identified. Our review found that few psychosocial factors have been studied and results were predominantly inconclusive. We observed heterogeneity amongst studies with respect to study duration and assessment methods. Binge eating disorder, mood disorders, and anxiety disorders have not reliably predicted weight loss in identified studies. Preliminary results suggest that psychosocial support is an important predictor of postoperative weight loss and highlight a likely role for pre- and post-surgery support groups. Conclusion: Social support, current or lifetime Axis I disorder, and post-operative loss of control over eating have been identified as important predictors of weight loss post-RYGBS. Larger, long-term studies are needed to further elucidate psychosocial risk factors for weight loss post-RYGBS
Keywords: psychosocial predictors